The Effect of SFL-Based Genre Pedagogy on EFL Learners’ Oral Reproduction in terms of Accuracy: a Mixed-Method Study - Sarmadi Kia, Farshid; Asadi, Nader; Zoghi, Masoud (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aims to examine the impact of Systemic Functional Linguistics (SFL)-based genre pedagogy on the oral reproduction accuracy of English as a Foreign Language (EFL) learners. Methodology: The research employed a mixed-method design, incorporating both quantitative and qualitative approaches. A total of 60 intermediate EFL learners, both female and male, were initially selected through the Oxford Quick Placement Test (OQPT). Based on the results, 38 participants were chosen and randomly assigned to an experimental or control group through convenience sampling. The accuracy of oral reproduction was assessed using Bygate’s (2001) framework, which measures the number of words per t-unit, including nouns, adverbs, adjectives, and verbs. Short stories were used as materials for the pre-test and post-test assessments. The experimental group received instruction through SFL-based genre pedagogy, while the control group was taught using traditional methods. Two independent raters evaluated and scored the oral reproductions. Findings: The study found that participants in the experimental group, who were taught using the SFL-based genre approach, showed greater improvement in oral reproduction accuracy compared to those in the control group. Additionally, the qualitative analysis revealed four significant themes: increased awareness of narrative genre structures, enhanced linguistic competence and its transferability, heightened self-confidence in oral reproduction, and positive attitudes towards SFL-based genre instruction. Conclusion: SFL-based genre pedagogy significantly enhances the oral reproduction accuracy of EFL learners. The findings suggest that this approach not only improves linguistic competence but also positively influences learners' confidence and attitudes towards language learning. These insights are valuable for EFL educators, curriculum designers, and program developers.